Contactless Yagi-patch EMG electrodes design and development for prosthetics. Issue 2 (8th December 2017) - Stopforth, Riaan; Mangezi, Andrew
Abstract : Purpose: A contactless electromyography (EMG) electrodes design and development for prosthetics, particularly the Touch Hand 3, was the main objective of this paper. The correlation between EMG electrodes and patch antenna are described, with the problem relating to the dimensions of the covidien electrodes. The purpose of this paper is to improve the signal strength of the EMG electrodes and having them to not be in contact with the skin to cause irritation in the person. Design/methodology/approach: A combination of the contact covidien electrodes and aluminium foil was used to develop electrodes that were in a similar configuration than a Yagi antenna. Different layers of patch elements were designed, developed and implemented. Findings: Different layers of Yagi-patch electrodes are tested with different volunteers and compared with the average signal strengths obtained from the covidien electrodes. An improvement in signal strength with the Yagi-patch electrodes has been found. Practical implications: The purpose of the work was to design, develop and test EMG electrodes that are cost-effective, reusable and able to improve the signal strengths that are recorded, for better functionality of prosthetic devices. Originality/value: The integration of EMG and antennae theory to implement a Yagi-patch EMG electrode to improve on signal reception. The electrodes have the properties of being cheap, easy available, can eliminate direct contact and avoiding patches on the skin. Comparison of different layered electrodes with the contactless electrodes close to the skin. Comparison of the different electrodes on a silicone sleeve, which are commonly worn by amputees, placed between the skin and the prosthetic's socket. Testing the Yagi-patch electrodes with an application with the prosthetic Touch Hand, to allow for the control of a system such as the Touch Hand.